The Effect of Utilizing Kaliandra Leaf (Calliandracalothyrsus) Meal Fermentation Using Cow Rumen Liquor on Diets for Growth of Tambaqui (Colossomamacropomum) - Ronna Ginting; Indra Suharman; Adelina Adelina (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACT The research was conducted during 56 days from May to July 2018, it is located in Fish Hatchery and Breeding Laboratory, SeiTibun, Kampar, Riau. This study aims to know the growth of tambaqui (Colossomamacropomum) fingerling which is given the artificial feed consist of kaliandra leaf meat fermented using cow rumen liquor.The method used in this study is the experimental method using a completely randomized design (RAL) with five treatments and three replications. This research need 300 fingerlings of tambaqui (initial weight 0,7-1 g and length 2-3 cm). Fish were reared in 1m3 in cages with stocking density approximately 20/cage. Feeding trials were replacing soybean meal with kaliandra leaf fermentation applied to P1(0%), P2(30%), P3(40%), P4(50%) and P5(60%) respectively for 35% of protein content.The result showed that fermentation kaliandra leaf has significant effect (P<0,05) in digestibility, feed efficiency, protein retentionand specific growth rate. Replacement  50% of kaliandra leaf fermented is the best response for producing the highest specific growth rate 5,9%, feed efficiency 54,4%, protein retention 66,42%, digestibility 78,63% and survival rate 100%. Based on the result of present research, replacement 50% level ofkaliandra leaf meal fermented as soybean meal substitution is recommended in pradical diet of tambaqui fingerling for growth performance. The water quality parameters consist of temperature about 23,4-30oC, power Hydrogen (pH) 5-5,6 and dissolved oxygen at 4-5 ppm. Keyword:Colossomamacropomum, Water Hyacinth, Fermented, Kaliandra Meal